Estudo de antenas patches de microfita miniaturizadas em banda larga para aplicação em dispositivos móveis e portáteis - Morais, José Haroldo Cavalcante de (2011)
This work presents techniques used to design and manufacture microstrip patch antennas for applications in portable and mobile devices. To do so, are evaluated several factors that can influence the performance of microstrip patch antennas. Miniaturization techniques are studied and employed in order to apply this type of antenna in mobile and / or mobile. The theories of microstrip patch antennas are addressed by analyzing characteristics such as constitution, kinds of patches, substrates, feeding methods, analysis methods, the main advantages and disadvantages and others. Techniques for obtaining broadband microstrip patch antennas were surveyed in literature and exemplified mainly by means of simulations and measurements. For simulations of the antennas was used the commercial software . In addition, antenna miniaturization techniques have been studied as a main concern the fundamental limits of antennas with special attention to electrically small antennas because they are directly linked to the microstrip patch antennas. Five design antennas are proposed to demonstrate the effectiveness of techniques used to obtain the microstrip patch antennas broadband and miniaturized for use in mobile devices and/or portable. For this, the proposed antennas were simulated, built and measured. The antennas are proposed to be used in modern systems of wireless communications such as DTV, GPS, IEEE 802.16, IEEE 802.11, etc. The simulations of the antennas were made in business and computer programs. The measured results were obtained with a parser Vector of networks of the Rhode and Schwarz model ZVB 14